Razgradnja starih automobila - Štrumberger, Nada (Promet - Traffic&Transportation, 2012)
There are more than 100 million cars driving on the roadsof Europe, and as many as 40 million only in Germany. Theaverage driving life of an automobile is 13 years. In Gemwnyabout 2.8 million cars are discarded annually, and in Europemore than 10 million passenger cars.In taking care of the old cars, the question is whether toseparate the precious metals from the catalytic converters, as itis known that the car manufacturers have had to install catalyticconverters in the cars in the EC countries starting from JS'April 1993, in order to reduce the harmful exhaust emissions.Collecting of catalytic converters and retrieving of preciousmetals has first started in Europe in 1971. By the year 1994 thequota was estimated at about 450 kg of platinum and 90 kg ofrhodium, and these numbers are expected to increase gradually.A car is not a homogeneous thing. By disassembling it, themetal elements reach the foreseen quota of reusability. There isa greater problem with non-metals, one part of which ends upat the dumping place. The car users take out from the old carpartly the propelling fluid and the cars are disassembled intosingle parts that are being sold directly or recycled. Takingcare of cars has not been organized up to now. The owner hadto pay taxes for that, according to the car type.The system of providing for the cars in the future should bea network one. A network system achieves in cooperation withthe existing car owners a regionally demarcated disassemblingnetwork. The network system takes over, apart from networkdistribution, also the future coordi1wtion net and forms a connectingpoint for the car manufacturers and the recycling ofsecondary raw materials.